Technological trajectory of electricity markets in Central America - Vargas-Alfaro, Leiner (2015)
This article presents a characterization of the institutional forms in the Central American electricity market for three country models: Guatemala, El Salvador, and Costa Rica. For this purpose, an analysis of the existing regulatory schemes related to the electricity sector in the region is carried out to explain the impact that the technological trajectory has on these models. This is important, not only because of the pattern of dependence and technological concentration of the countries with respect to energy sources (electricity and fuels) based on fossil fuels, but also because of the effect and vulnerability that the high concentration and dependence -stickness- of electricity generation and transportation technologies based on these fuels has on climate change. A shift towards fossil fuel-based electricity sources is evident in those countries that have opted for market reforms with short-term incentives.